Can a woman do it? On the search for identity and a sense of belonging in the novel Air-Roots by Ruth Almog (Revista de Estudos Orientais, 2010)
This article deals with the novel AIR-ROOTS by Ruth Almog, which was published in Israel in 1987. This novel is distinguished from Almog's previous work in its attempt to tackle new themes. For the first time, Almog portrays a feminine character who is a political activist; through her the author deals with the political-social-ideological questions related to the state of Israel. Mira Gutman, the heroine, grew-up in one of the first Jewish settlements. Her father dedicated himself to serve the country and left her with a mentally ill, suicidal mother. The story shows Mira's search for identity and a place in the world as a woman and an Israeli. The end of the novel implies that Mira would be able to find her identity and place in the world, only when she would return to Israel and renew her attempt to write her greatgrandfather's story. Through researching his life and opinions she would also find a way to involve herself in the crucial political problem of Israel: the Jewish-Palestinian conflict. In conclusion, the novel presents a woman who wants to be heard regarding the "big" issues, but she needs the help of a man (her great-grandfather) to do so.